2017
DOI: 10.1093/ejcts/ezx092
|View full text |Cite
|
Sign up to set email alerts
|

Stage I non-small-cell lung cancer: long-term results of lobectomy versus sublobar resection from the Polish National Lung Cancer Registry†

Abstract: Wedge resection was associated with significantly lower 3-year and 5-year survival rates compared to the other methods of resection. There was no significant difference in 3-year or 5-year survival rates between lobectomy and segmentectomy. Segmentectomy, but not wedge resection, could be considered an alternative to lobectomy in the treatment of patients with Stage I NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 16 publications
1
52
1
1
Order By: Relevance
“…Figure a illustrates the predicted five year survival rate after lobectomy. Outcomes from real studies are marked by gray dots . In real studies, the median age of each cohort was set to a representative value of age at diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a illustrates the predicted five year survival rate after lobectomy. Outcomes from real studies are marked by gray dots . In real studies, the median age of each cohort was set to a representative value of age at diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Lobectomy is undoubtedly the standard of care for operable early‐stage NSCLC in the current situation where there are no randomized trials comparing SABR with lobectomy. However, most of the previously reported studies on lobectomy included young patients with an average age of 65 years, while those on SABR included older patients with an average age of 75 years . As a result, it is difficult to compare the overall survival between the two procedures directly using the existing research designs including patients of different age distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Lobectomy combined with systematic lymph node (LN) dissection or sampling currently is the treatment of choice for patients with NSCLC. However, increasing evidence has emerged from institutional case series and national registry to Original Article Appropriate lymphadenectomy significantly reduced recurrence after segmentectomy for patients with non-small cell lung cancer support the equivalency in the long-term survival between segmentectomy and lobectomy for small-sized earlystage NSCLC (2)(3)(4)(5)(6). Segmentectomy is chosen for the well-selected patients, for its advantage of preserving lung parenchyma, pulmonary function and a chance of future resections for secondary primary lung cancer (7).…”
Section: Introductionmentioning
confidence: 99%
“…In several observational studies, lobectomy and segmentectomy has shown comparable long-term outcomes in stage I NSCLC less than 2 cm in diameter (3,4). Most of the studies shows similar outcomes in lobectomy and sublobar resection but there are contradictory results when wedge resection and segmentectomy are analyzed separately.…”
mentioning
confidence: 99%
“…According to Altorki et al a wedge resection and segmentectomy is associated with comparable outcome for patients with small cT1N0 NSCLC (5). In retrospective observational study of Dziedzic et al, which assessed the results of treatment of stage I NSCLC, wedge resection was associated with significantly worse five-year survival rate compared to lobectomy and segmentectomy (4). What may be the difference between wedge and segmental resection is the resection margin and hilar and mediastinal…”
mentioning
confidence: 99%